Al-Ta’wīl al-‘Ilmī: Kearah Perubahan Paradigma Penafsiran Kitab Suci - M. Amin Abdullah (Al-Jami'ah Research Centre, 2001)
This article tries to describe al-ta'wil al-'ilmī approach as an alternative model of exegeses on text by using Hermeneutic circle which dialogize exactly between paradigms of Bayani epistemology nd paradigm of irfani epistemology. According to the writer al-ta'wil al-'ilmī cannot be developed on either parallel or linear relation pattern. This is because parallel relation pattern cannot open newly transformable horizon, views and ideas. Each epistemology stops and remains at its own position and has difficulty in dialoging between one kind of epistemology and others. Like a railway, these three epistemologies will remain at each own track and will not meet in a convergent point. Whereas linear relation pattern that assumes that there is finality will trap someone or a group of people on exclusive-polemic-dogmatic situation. Linear relation pattern will regard other kinds of epistemology as not valid. Then, he/she will enforce one of epistemologies that has been habit of mind to be implemented at the expense of inputs from other epistemologies. Therefore, he/she is easily trapped into truth claim, i.e. to regard that it is only its own kind of epistemology that is right, while others are wrong. Contemporary approach of Islamic studies and conventional Ulumuddin is, according to the writer, can only take scholars and students of religious sciences to a choice between one of the two forms of above relation of scientific epistemology. Both forms of choices are less conducive to take to one's Islamic maturity and even to Muslim community as a group. Both are easily trapped into communalism thought, especially if they are faced to problems of socio-religious relations in a pluralistic society. For this reason, this epistemology should be complement with relation pattern of the three existing epistemologies that offer alternative new way of thinking which are reformative, re-constructive and transformable. This is regarded as circular relation, this means that each epistemology of Islamic studies used in Islamic studies can recognize its limitation and weaknesses and at the same time, can take advantage of inventions offered by other scientific tradition as well as have ability to make up the weaknesses which embody in its own.